A new polyazomethine-based pyrazole moiety and its reinforced nanocomposites @ ZnO for antimicrobial applications - Aqilah A. Hakami; Hajar S. Alorfi; Thoraya A. Farghaly; Mahmoud A. Hussein (Designed Monomers and Polymers)
A new class of biologically active polyazomethine/pyrazole and their related nanocomposites, polyazomethine/pyrazole/zinc oxide nanoparticles, have been successfully synthesized through the polycondensation technique in the form of polyazomethine pyrazole (PAZm/Py4–6) and polyazomethine/pyrazole/zinc oxide nanoparticles (PAZm/Py/ZnOa-c). The polymeric nanocomposites were prepared with a 5% loading of zinc oxide nanofiller using the same preparation technique, in addition to the help of ultrasonic radiation. The characteristics of the new polymers, such as solubility, viscometry, and molecular weight, were examined. All the polymers were completely soluble in the following solvents: concentrated sulfuric acid, formic acid, dimethylformamide, dimethyl sulfoxide, and tetrahydrofuran. Furthermore, the weight loss of the polyazomethine pyrazole (4, 5, and 6) at 800 °C was 67%, 95%, and 86%, respectively, which indicates the thermal stability of these polymers. At 800 °C, the polyazomethine/pyrazole/zinc oxide nanoparticles (a, b, and c) lost 74%, 68%, and 75% of their weight, respectively. This shows that adding zinc oxide nanoparticles made these compounds more stable at high temperatures. The X-Ray diffraction pattern of the polyazomethine pyrazole (PAZm/Py4–6) shows a number of sharp peaks with varying intensities. The polymers that were studied had straight crystal structures. Furthermore, the measurements of polyazomethine/pyrazole/zinc oxide nanoparticles (PAZm/Py/ZnOa-c) indicate a good merging of zinc oxide nanoparticles into the matrix of polymers. The antimicrobial activity of polymers and polymer nanocomposites was tested against some selected bacteria and fungi. The synthesized polymer (c) shows the highest activity against the two types of gram-negative bacteria selected. Most tested compounds were found to be effective against gram-positive bacteria except polyazomethine pyrazole (PAZm/Py5) and polyazomethine pyrazole (PAZm/Py6), which do not exhibit any activity. The synthesized polymers and their related nanocomposites were tested for their ability to kill the chosen fungi. All of them were effective against Aspergillus flavus, but only polyazomethine pyrazole (PAZm/Py4) and polyazomethine/pyrazole/zinc oxide (PAZm/Py/ZnOc) were effective against Candida albicans.